Pembelajaran Dan Pelatihan Buku Super Cepat Belajar Calistung Di Tk Muslimat Al-Khoiriyah Desa Mojodanu - nasirudin, mohamad; Ashar, Salim; Bajuri, Mohammad Fahmi; Febrianti, Arista Sasa Bela; Khanifah, Dian; Fitroh, Mayada Fatwatul; Khasanah, Kharisma Wahyu; Khakim, Achmad Latif Nur (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2025)
The book "Super Fast Learning Calistung" is specifically designed to help children learn the basics of reading, writing and arithmetic (calistung) in a fun, effective and interactive way. This book presents a variety of activities and exercises arranged in a structured manner, making it easier for children to understand the concept of calistung from an early age. One of the advantages of this book is its interactive approach and educational games designed to stimulate children's interest in learning, making it a process that is not only educational, but also entertaining. Through an organized learning method, this book not only focuses on children as learners, but also involves parents and teachers as companions in the learning process. The community service approach in Mojodanu Village uses the Service Learning (SL) method, which is carried out in the form of mentoring or tutoring to support learning. The training provided to parents and teachers aims to equip them with the right strategies in accompanying children when using this book, ensuring children can understand the material well and apply calistung skills in everyday life. This book is also designed to increase children's motivation and interest in learning on an ongoing basis, with the hope that they can master calistung skills solidly. With a strong foundation in reading, writing and arithmetic, children are expected to be ready to face further educational challenges and achieve success in the future.